2013
DOI: 10.1063/1.4773470
|View full text |Cite
|
Sign up to set email alerts
|

Selective homopolymer adsorption on structured surfaces as a model for pattern recognition

Abstract: Homopolymer adsorption onto chemically structured periodic surfaces and its potential for pattern recognition is investigated using Monte Carlo simulations. To analyze the surface-induced selective adsorption on a fundamental geometric level polymer chains are represented by freely jointed chains with a fixed bond length whose monomers are attracted by the sites of regular lattice patterns. The structural properties of the adsorbed low-temperature state are comprehensively discussed for different lattices by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, a considerable number of coarse-grained (where several atoms can be consolidated into a single, typically spherical, interaction site) simulation studies of the abiotic/biotic interface have been reported. ,, Coarse-grained force fields enable the access of greater simulation length-scales and time-scales, but this reduction in computing demand comes with the sacrifice of atomistic details arising from the coarse-graining. Such coarse-grained approaches provide a simplified description of the biointerface that is computationally cheaper to realize compared with all-atom force fields, which can be particularly advantageous when applied to the study of multipeptide adsorption or in making very broad estimates of thermodynamic quantities such as the heat capacity of the system. ,,,, This means that the key advantage of coarse-grained force fields lies in their ability to recover relatively simple structural information, particularly when applied to surface-adsorbed multipeptide overlayers. However, the prospect of identifying and using coarse-grained force fields to reliably capture the IDP-like conformational character of materials-binding peptides is unresolved and remains an ongoing challenge .…”
Section: Bioinspired Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a considerable number of coarse-grained (where several atoms can be consolidated into a single, typically spherical, interaction site) simulation studies of the abiotic/biotic interface have been reported. ,, Coarse-grained force fields enable the access of greater simulation length-scales and time-scales, but this reduction in computing demand comes with the sacrifice of atomistic details arising from the coarse-graining. Such coarse-grained approaches provide a simplified description of the biointerface that is computationally cheaper to realize compared with all-atom force fields, which can be particularly advantageous when applied to the study of multipeptide adsorption or in making very broad estimates of thermodynamic quantities such as the heat capacity of the system. ,,,, This means that the key advantage of coarse-grained force fields lies in their ability to recover relatively simple structural information, particularly when applied to surface-adsorbed multipeptide overlayers. However, the prospect of identifying and using coarse-grained force fields to reliably capture the IDP-like conformational character of materials-binding peptides is unresolved and remains an ongoing challenge .…”
Section: Bioinspired Nanotechnologymentioning
confidence: 99%
“…Such coarse-grained approaches provide a simplified description of the biointerface that is computationally cheaper to realize compared with allatom force fields, which can be particularly advantageous when applied to the study of multipeptide adsorption 154−157 or in making very broad estimates of thermodynamic quantities such as the heat capacity of the system. 128,134,150,152,153 This means that the key advantage of coarse-grained force fields lies in their ability to recover relatively simple structural information, particularly when applied to surface-adsorbed multipeptide overlayers. However, the prospect of identifying and using coarse-grained force fields to reliably capture the IDP-like conformational character of materials-binding peptides is unresolved and remains an ongoing challenge.…”
Section: Advances In Computational Approaches To Examine Nanoparticle...mentioning
confidence: 99%
“…This implies, in particular, that the interaction potentials are soft, i.e., molecules can penetrate each other. Although the Edwards models were originally introduced in the context of analytical theory [22], they also proved to be efficient models for computer simulations [16,[23][24][25]. The partition function of an Edwardstype model can be rewritten exactly as a fluctuating field theory [26], either by applying a Hubbard-Stratonovich transformation (if the interactions are purely quadratic in the densities), or, more generally, by inserting unities (delta functions) in a Faddeev-Popov way [27][28][29][30].…”
Section: Basic Concept Of the Approachmentioning
confidence: 99%
“…The construction of our hybrid scheme starts from particle resolution (PR) models of the Edwards type [40], in which the interactions are expressed in terms of local densities. Edwards type models are popular starting points in theoretical polymer physics [41][42][43][44][45] and are often used for the interpretation of experimental phenomena in soft matter and biophysics, as well as for efficient particlebased computer simulations [46][47][48][49][50]. In our adaptive res-olution approach, we exploit the fact that the partition function of Edwards models can be rewritten exactly as a fluctuating field theory.…”
Section: Introductionmentioning
confidence: 99%